The independence of the speaker : the Westminster model and the Australian experience - Rahman, Md. Nojibur, 1960-; Bangladesh Institute of Parliamentary Studies (Dhaka : Bangladesh Institute of Parliamentary Studies, 2000)
With reference to Australia, England and Bangladesh.
Bibliography: p. 83-88.
Keywords: Bangladesh -- Jatiya Samsada -- Speaker; Great Britain -- Parliament -- Speaker; Australia -- Parliament -- Speaker; Representative government and representation -- Cross-cultural studies